Forming the Disciplinary Character of Santri through Rules of Procedure - Siti Nurjanah; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2022)
Madrasah Diniyah Takmiliyah Awaliyah (MDTA) plays an important role in building the character of students, Ustadz and Ustadz have an obligation to foster, supervise so that students have a disciplined character. Discipline must be implemented in students so that MDTA Miftahul Ula students have self-control, not doing things that deviate. This study uses the Participation action research (PAR) method, this research is collaborative. The focus of the research is on the implementation of discipline in shaping the disciplined character of students at MDTA Miftahul Ula by implementing madrasa rules. Steps to collect data through observation, interviews, and documentation. Data analysis with data reduction data, data display, and data verification. As for the results of the study, MDTA Miftahul ula in forming the disciplined character of the students: first, making rules, secondly socializing and implementing rules and regulations in the madrasa environment and thirdly, there is supervision of students, while actions that violate the rules will be subject to sanctions, and those who violate the rules will be punished. second, there is a direct warning from the ustadz/ustadzah who teaches in the class (the homeroom teacher).